Household clustering and seasonal genetic variation of Plasmodium falciparum at the community-level in The Gambia - Marc-Antoine Guery; Sukai Ceesay; Sainabou Drammeh; Fatou K Jaiteh; Umberto D'Alessandro; Teun Bousema; David J Conway; Antoine Claessens (eLife)
Understanding the genetic diversity and transmission dynamics of Plasmodium falciparum, the causative agent of malaria, is crucial for effective control and elimination efforts. In some endemic regions, malaria is highly seasonal with no or little transmission during up to 8 mo, yet little is known about how seasonality affects the parasite population genetics. Here, we conducted a longitudinal study over 2.5 y on 1516 participants in the Upper River Region of The Gambia. With 425 P. falciparum genetic barcodes genotyped from asymptomatic infections, we developed an identity by descent (IBD) based pipeline and validated its accuracy against 199 parasite genomes sequenced from the same isolates. Genetic relatedness between isolates revealed a very low inbreeding level, suggesting continuous recombination among parasites rather than the dominance of specific strains. However, isolates from the same household were sixfold more likely to be genetically related compared to those from other villages, suggesting close transmission links within households. Seasonal variation also influenced parasite genetics, with most differentiation occurring during the transition from the low transmission season to the subsequent high transmission season. Yet chronic infections presented exceptions, including one individual who had a continuous infection by the same parasite genotype for at least 18 mo. Our findings highlight the burden of asymptomatic chronic malaria carriers and the importance of characterizing the parasite genetic population at the community-level. Most importantly, ‘reactive’ approaches for malaria elimination should not be limited to acute malaria cases but be broadened to households of asymptomatic carriers.